Power and Resistance in The Gifted Thai Series - Terryna Pramesthi Rizmadhani; Theophilus Joko Riyanto (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This study applies Michel Foucault’s theory of power and resistance to explore how the school maintains control over students and how the students fight back. It reveals how the school uses power/knowledge to create rules and disciplinary power to enforce the system and rules in maintaining control. Students resist through micro-resistance by questioning the system and rules, and through strategic, tactical, and counter-conduct resistance by protesting the system and rules. The analysis shows the school establishes control by informing and threatening students, and by intimidating and punishing them. To resist, students question the rules in the conversations with friends and the headmaster, and protest by breaking the teacher’s metronome and complaining to the government. This study concludes that the school’s use of violence to maintain power contradicts Foucault's concept of power and leads to students' resistance, highlighting their desire for a fairer environment.